Determinants of the practice of financial management by rural producers in the microregion of Salgueiro, Brazil (Research, Society and Development, 2021)
The aim of this study is to analyze the determinants of financial management of rural farmers in the microregion of Salgueiro, Brazil. Primary data collected through a survey method were used, using a questionnaire with rural producers in the micro-region of the municipality of Salgueiro. From the logistical analysis, it was possible to evidence that the higher education and behaviors related to the operational and strategic planning practices of the rural producers in that region has positively influenced the greater tendency towards financial management practices. On the other hand, structured rural enterprises of the family farming type have a lower tendency towards these practices, demonstrating the need for public policy actions that foster greater qualification for this population in the region.